Caribou and Man - Couturier, Serge; Ginhoven, Quentin van (Rangifer, 2003)
From April 23 to 27, 2001, more than 230 caribou experts migrated to the 9th North American Caribou Workshop, held at the tree-line in the Inuit town of Kuujjuaq, Nunavik, Québec. This community of about 1800 people near Ungava Bay was chosen over larger cities in southern Québec following a survey of potential workshop participants. Holding the conference in such a particularly appropriate location was made possible by the sustained efforts of the Organizing and Scientific Committees, by the help of the sponsors, and, above all, by the tremendous support of the people of Kuujjuaq. Keeping in mind the importance of caribou to the local people and the fact that development and other fast-growing human activities have today reached the North—for many southerners, the last frontier—the theme chosen for the 9th North American Caribou Workshop was also particularly appropriate: Caribou and Man.